Slow release urea nitrate with starch polymer coating technique for fermentation and rumen digestibility in vitro - Yasmin Nurul; Apriani Vita; Silviani Ema; Jayanegara Anuraga (BIO Web of Conferences)
The present study was aimed to evaluate the effect of starch polymer coating. The starch used are divided into two, i.e., sago starch and cassava starch. A randomized complete block design was utilized in this study consisted of five treatments and four replications. The treatments are T0 = control diet; T1 = T0 + uncoated urea; T2 = T0 + uncoated urea-nitrate; T3 = T0 + urea- nitrate with sago starch coating; T4 = urea-nitrate with cassava starch coating. The urea-nitrate supplementation treatments with starch coating were expected to enhance dietary crude protein by 2% of the control diet and slow down the release of the diet in the rumen. Results revealed that T4 treatments reduced ammonia concentration compared to T0, T1, T2, and T3 (P<0.05). However, other parameters such as rumen pH, volatile fatty acid, microbial protein synthesis, dry matter digestibility, organic matter digestibility, total gas production, and methane production were similar among the treatments. In conclusion, the urea-nitrate supplementation with cassava starch coating in ruminant diet might slow down the release of ammonia in the rumen in vitro.